Perancangan Web Blogger untuk Meningkatkan Branding UMKM Warung Ajja - Cinta Hanaya; Najwa Febry Hardiyessi; Novadilastri Novadilastri; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Warung Ajja is a culinary MSME that requires a branding strategy to increase its competitiveness. The use of digital technology through the Blogger platform offers an affordable, accessible, and effective solution. This study aims to design a Blogger-based website to introduce products while building the brand image of Warung Ajja. The methodology applied is a qualitative approach through interviews with the business owner and direct observation. The results of this research show that the website helps the MSME present its business identity more professionally, provide clear product information, and expand promotional reach. The use of Blogger has proven to increase the digital visibility of Warung Ajja.